Representasi Akad Mudharabah dalam Dokumen Produk Tabungan Bank Syariah : Analisis Kesesuaian dengan Fatwa DSN-MUI - Kusnandar Kusnandar; Sudin Haron; Nanang Lidwan; Vivi Afifah (Matan : Journal of Islam and Muslim Society, 2026)
This study analyzes how the mudharabah contract is represented in Islamic banking savings products by examining official product documents and evaluating them against the normative provisions of the DSN-MUI (Dewan Syariah Nasional Majelis Ulama Indonesia) fatwas on mudharabah and savings. Using a qualitative approach with content analysis, the research reviews documents published on the official websites of several Islamic banks in Indonesia. The analysis focuses on contract clarity, the profit-sharing ratio (nisbah), fund management authority, and transparency regarding loss risk. Findings show that, formally, products declare mudharabah mutlaqah and apply profit-sharing in line with the fatwas. Substantively, however, product documents simplify key fiqh elements, particularly the negotiation of nisbah and the explanation of loss risk borne by the shahibul mal. Documents tend to emphasize potential returns rather than educating customers on the contract’s principles. The study reveals a gap between classical fiqh concepts, fatwa norms, and their representation in modern banking documents, highlighting how fiqh-based contracts are transformed within contemporary Islamic banking products.